153k views
2 votes
Someone please answer this

Someone please answer this-example-1

1 Answer

4 votes

Answer:

(x - 1)(5x - 6)

Explanation:

Given

5x² - 11x + 6

Consider the factors of the product of the coefficient of the x² term and the constant term (ac) which sum to give the coefficient of the x- term (b)

ac = 5 × 6 = 30 and b = - 11

The factors are - 5 and - 6

Use these factors to split the x- term

5x² - 5x - 6x + 6 ( factor the first/second and third/fourth terms )

= 5x(x - 1) - 6(x - 1) ← factor out (x - 1) from each term

= (x - 1)(5x - 6)

User Jan Ariel San Jose
by
5.5k points